Nobody likes a rat: On the willingness and consequences of reporting lies - Ernesto Reuben; Matt Stephenson (Institute for the Study of Labor (IZA), 2012)
We investigate the intrinsic motivation of individuals to report, and thereby sanction, fellow group members who lie for personal gain. We further explore the changes in lying and reporting behavior that result from giving individuals a say in who joins their group. We find that enough individuals are willing to report lies such that in fixed groups lying is unprofitable. However, we also find that when groups can select their members, individuals who report lies are generally shunned, even by groups where lying is absent. This facilitates the formation of dishonest groups where lying is prevalent and reporting is nonexistent.
Keywords: D03; K42; M42; M14; C92; 330; lying; lying aversion; whistleblowing; social norms; dishonesty; Betrug; Whistleblowing; Soziale Norm; Soziale Gruppe